ANNUAL STATISTICAL ANALYSIS OF CARDIOVASCULAR MORTALITY IN SEISMICALLY UNSTABLE REGIONS OF AZERBAIJAN - Afandiyeva, L.Q.; Sadigova, T.A.; Alekperova, A.K.; Mammadli, S.M.; Mammadyarova, K.F.; Kerimova, E.Z. (World of Medicine and Biology, 2024)
With the purpose to examine the influence of geophysical and seismic parameters in unstable regions of Azerbaijan on mortality rates from cardiovascular pathologies the medical records of 4,043 patients were analyzed. The number of deaths, their causes, distribution by gender and age were assessed, and a relationship was established with the magnitude of earthquakes, the depth of the epicenter and seismological activity. Earthquakes with a magnitude of 1.1–2.0 and a depth of less than 10 km, significantly impacted mortality rates. Individuals with cardiovascular pathologies have a 1.63 times higher risk of death due to an earthquake compared to those without such pathologies. Persons with cardiovascular diseases have 2.67 times the odds of dying compared to those without such pathologies. Cardiovascular pathologies account for 5.79 % of the variation in overall mortality among all causes. These results indicate that cardiovascular pathologies significantly increase the risk of death.
Keywords: cardiovascular pathology; mortality; earthquake; seismic parameters